Water stability of soil aggregates in different systems of tillage - Jaroslava BARTLOVÁ; Barbora BADALÍKOVÁ; Lubica POSPÍŠILOVÁ; Eduard POKORNÝ; Bořivoj ŠARAPATKA (Soil and Water Research, 2015)
The influence of various agrotechnical measures on macrostructural changes in topsoil and subsoil was studied in the course of a four-year experiment. Macrostructure was evaluated according to the ability of soil aggregate to resist degradation. Three variants of soil tillage were established: ploughing to a depth of 0.22 m, reduced tillage (subsoiling to 0.35-0.40 m, and shallow disking of soil to a depth of 0.15 m). For observation, three locations were chosen in various production areas of the Czech Republic with differing soil and climatic conditions. In these locations crops were grown under the same crop rotation: rapeseed (Brassica napus L.), wheat (Triticum aestivum L.), maize (Zea mays), wheat (Triticum aestivum L.), and barley (Hordeum vulgare). After four years of different tillage, a change in the water stability of soil aggregates (WSA) was evident. It was found out that reduced tillage of soil positively influenced both the WSA and the yield of the crops grown. A relationship of positive dependence between WSA, the content of humus substances, and cation exchange capacity of soil was also found. According to the obtained results, for agricultural practice a classification scale of structural quality was proposed on the basis of statistics of one variable (average, its mean error and distribution normality).